Evaluation of 30-day mortality rate following intravenous systemic anticancer therapy: a retrospective analysis - Taha Enes Cetin; Osman Sutcuoglu; Orhun Akdogan; Gozde Savas; Nazan Günel; Aytug Uner; Nuriye Ozdemir; Ahmet Ozet; Ozan Yazici (BMC Cancer)
Abstract Introduction This study aims to determine the 30-day mortality rate following intravenous systemic anticancer therapies (SACT) and to compare mortality rates between different therapeutic modalities, including immunotherapy, monoclonal antibodies, and chemotherapy. Materials and methods A retrospective analysis was conducted on cancer patients who received intravenous SACT between January 1, 2022, and December 31, 2022. Patient data, including demographics, cancer types, treatment details, and mortality outcomes, were collected from hospital records. The primary endpoint was 30-day mortality following the last dose of SACT. Results Among the 1,937 patients included, the overall 30-day mortality rate post-SACT was 7%. Significant factors affecting 30-day mortality included Eastern Cooperative Oncology Group (ECOG) performance status, body mass index (BMI), and smoking status. In Non-Stage 4 treated patients, a higher ECOG score was significantly associated with increased mortality. In Stage 4 treated patients, both a higher ECOG score and a lower BMI were independent predictors of increased mortality. Additionally, receiving Stage 4 treatment and being an active smoker significantly increased mortality risk in patients with gastrointestinal and breast cancers. Conclusion Monitoring 30-day mortality post-SACT is essential for improving oncological care quality. Identifying and addressing modifiable risk factors and carefully selecting patients for modern oncological treatments can help reduce mortality rates. Further prospective studies are warranted to explore the impact of immunotherapy on short-term mortality in diverse cancer populations.